2004
DOI: 10.1007/s00442-004-1695-z
|View full text |Cite
|
Sign up to set email alerts
|

Complex interactions between native and invasive fish: the simultaneous effects of multiple negative interactions

Abstract: We suggest that the ultimate outcome of interactions between native species and invasive species (extinction or coexistence) depends on the number of simultaneous negative interactions (competition and predation), which depends on relative body sizes of the species. Multiple simultaneous interactions may constrain the ability of native species to trade fitness components (i.e., reduced growth for reduced risk of predation) causing a spiral to extinction. We found evidence for five types of interactions between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
188
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(201 citation statements)
references
References 39 publications
8
188
1
4
Order By: Relevance
“…In addition, other studies have demonstrated that interaction with mosquitofish causes alterations in the biological parameters of native species, such as growth or recruitment (e.g. Howe et al 1997, Mills et al 2004). …”
Section: Discussionmentioning
confidence: 99%
“…In addition, other studies have demonstrated that interaction with mosquitofish causes alterations in the biological parameters of native species, such as growth or recruitment (e.g. Howe et al 1997, Mills et al 2004). …”
Section: Discussionmentioning
confidence: 99%
“…The negative effects of invasive fish species on native fish, communities and ecosystems is widely recognized (Cambray, 2003;Mills et al, 2004). The impact of an invader like the bleak needs to be assessed at different levels: genetic pool (hybridization), individuals (changes in life history and behaviour), populations (changes in abundance and distribution of native fish species) and communities (competition, species richness, diversity and trophic structure).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the intro duction of non-native predatory sport fish, riverine environments have often experienced shifts in species assemblages towards non-native generalist species (Fischer & Paukert 2008). One such species that has been widely implicated in declines of native species is the western mosquitofish Gambu- (Lynch & Roh 1996, Haas 2005 and has affected species assemblages through predation, competition and harassment, leading to the reduction and elimination of fish species, aquatic invertebrates and amphibian communities around the world (Meffe 1985, Moyle 2002, Mills et al 2004, Zeiber et al 2008. Whether the western mosquitofish threatens the plains topminnow is not clear.…”
Section: Potential Threatsmentioning
confidence: 99%
“…The western mosquitofish has been implicated in the reduction of plains topminnow populations (Lynch & Roh 1996, Haas 2005 and has affected species assemblages through predation, competition and harassment, leading to the reduction and elimination of fish species, aquatic invertebrates and amphibian communities around the world (Meffe 1985, Moyle 2002, Mills et al 2004, Zeiber et al 2008. Whether the western mosquitofish threatens the plains topminnow is not clear.…”
mentioning
confidence: 99%